UNVEILING EMPLOYEE PERFORMANCE INFLUENCERS - Hermansyah, Hermansyah; Saladin, Khairani; Kahar, Azmen; Asrilsyak, Sharnuke (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study analyses how work environment comfort, leadership, time management and employee engagement affect employee performance. Data was collected randomly, with any individual who met the set criteria potentially being part of the sample. The results show that the work environment has an impact on employee engagement but not on employee performance. On the other hand, leadership and time management affect employee engagement and employee performance. In addition, employee engagement itself is significantly related to employee performance. This study concludes that leadership has the greatest influence in determining employee engagement and employee performance.